General public awareness of indications and complications of sleeve gastrectomy in Al’qassim region, Saudi Arabia - Alayaaf, Abdullah S.; Alsaeed, Hamad S.; AlSamani, Abdullah N.; Alfadhel, Emad A.; Aldhilan, Maha M.; Alswyan, Rabab A. (International Journal of Advances in Medicine, 2021)
Background: Obesity is risingly becoming a health care problem. After ineffective tries to lose weight with lifestyle-based conservative methods, the most effective obesity treatment will become bariatric surgery. Objective of this study aimed to assess the awareness of the general public about indications and complications of sleeve gastrectomy in Al’Qassim region, Saudi Arabia. Methods: This was a cross-sectional study conducted among the general population living in Al’Qassim region, Saudi Arabia. A validated Arabic/English questionnaires were distributed among the targeted individual using an online platform. Questionnaires included demographic data, general knowledge about gastric sleeve and the knowledge toward the indication and complication of sleeve gastrectomy. All statistical analyses were performed using SPSS version 26. Results: Nearly all participants were aware of sleeve gastrectomy (99.1%). The prevalence of participants who knew the indications and complications of sleeve gastrectomy were 60.9% and 72.2%, respectively. Furthermore, approximately three quarters (70.3%) were confident that the most common indication of the gastric sleeve was an adult with BMI >40 kg/m2. Statistical tests revealed that the knowledge toward the indication and complication of sleeve gastrectomy were more common among those who have heard about BMI and those who knew the BMI range of obese person (p<0.05). Conclusions: Although, general population awareness toward the indication and complication of sleeve gastrectomy was moderate, however, their knowledge about the BMI seems to be lacking. Having better knowledge about BMI likely influenced their awareness of the indications and complications of gastric sleeve.